Analysis of Employee Capacity Gap in Managing Network Security and Its Implementation Towards Insider Threat Prevention - Sitorus, Felix Noel; Harwahyu, Ruki (Institut Riset dan Publikasi Indonesia, 2025)
Network security is crucial for protecting organizational information in the rapidly evolving digital era. Threats to networks do not only come from external sources, such as malware or hacking, but also from within the organization, known as insider threats. These threats can cause significant losses, whether due to intentional or unintentional actions by employees or internal parties with access to the system. Therefore, employees' ability to manage network security is key to addressing these threats. Handling insider threats must be a top priority for organizations. This study aims to analyze the employee capacity gap in managing network security and its impact on preventing insider threats in XYZ Organization. By implementing ISO 27001 security standards, particularly within the context of the Information Security Management System (ISMS) using the PDCA approach, this research evaluates how human resource management relates to information asset management and network security maintenance. The findings indicate that gaps in employees' knowledge and skills regarding network security significantly contribute to vulnerabilities against insider threats. This study also highlights how the implementation of ISO 27001, which emphasizes asset analysis and the PDCA cycle, can help organizations improve information security governance and prevent insider threats